2013
DOI: 10.1161/circulationaha.113.003543
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Analysis of Trends in the Incidence and In-Hospital Mortality for Lower-Extremity Arterial Thromboembolism

Abstract: Background-Epidemiology data for lower-extremity arterial thromboembolism (LET) are limited and may result from either acute limb ischemia or an acute exacerbation of critical limb ischemia. Given marked changes in both diagnosis and therapy over the last 2 decades, we hypothesized that this time period would have witnessed reductions in both the incidence and in-hospital mortality of LET. Methods and Results-Data from 1988 through 2007 from the National Hospital Discharge Survey were analyzed. All admissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
1
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 21 publications
(29 reference statements)
1
28
1
3
Order By: Relevance
“…Yet, the risks of perioperative adverse events and postoperative death associated with operative revascularization performed in the setting of ALI remain high 5. With the advent of endovascular techniques and following the publication of randomized controlled trials in the 1990s suggesting that percutaneous thrombolysis is a less‐invasive yet comparable alternative to operative revascularization,6, 7, 8, 9, 10, 11, 12 ALI has been increasingly managed with endovascular peripheral vascular interventions (PVI) rather than open surgical approaches 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the risks of perioperative adverse events and postoperative death associated with operative revascularization performed in the setting of ALI remain high 5. With the advent of endovascular techniques and following the publication of randomized controlled trials in the 1990s suggesting that percutaneous thrombolysis is a less‐invasive yet comparable alternative to operative revascularization,6, 7, 8, 9, 10, 11, 12 ALI has been increasingly managed with endovascular peripheral vascular interventions (PVI) rather than open surgical approaches 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…Administrative databases, such as the National Hospital Discharge Survey, have been used 6,7 but have significant limitations for the analysis of ALI outcomes and cost. A validation study showed low specificity and positive predictive value of the diagnostic codes typically used in ALI analyses.…”
mentioning
confidence: 99%
“…A validation study showed low specificity and positive predictive value of the diagnostic codes typically used in ALI analyses. 7 However, diagnostic codes do not differentiate between ALI vs worsening of chronic limb ischemia or between embolic and nonembolic ALI, making estimations of incidence, in-hospital costs, and mortality unreliable. 7,8 Single-center studies of ALI have demonstrated that outcomes of interventions can differ significantly from those reported in RCTs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…По результатам недавно проведенного анализа 1,76 млн случаев госпитализаций пациентов с КИК и ОИК отме-чен положительный тренд по улучшению результатов лече-ния, однако уровень госпитальной летальности остается высоким -6%, а количество ампутаций достигает 7% [13].…”
unclassified